Advanced Strategies for Mitigating Postharvest Deterioration in Soft Fruits - Raza , Mohsin; Saleem , Muhammad Asad; Naseer , Mudassar; Farooq , Amjad; Ali , Shakir; Hafi , Abdul; Noor , Hafiz Usama; Rashid , Muhammad Hamdan; Shafquat , Iman (Indus Journal of Bioscience Research, 2024)
Preventing disease incidence in soft fruit post-harvest presents a substantial challenge. This study examines traditional methods and emerging technologies employed to address this issue. Conventional approaches typically regulate fruit ripening and pathogen proliferation through low-temperature storage and modified atmosphere techniques. Various methodologies such as irradiation, brief heat treatments, and chemical applications (e.g., calcium, 1-Methylcyclopropene, nitric oxide). Physical methods like heat treatments and irradiation promise to extend soft fruit’s shelf-life. Biological control and treatments that stimulate the fruit’s innate responses exhibit potential, particularly considering fungicide restrictions. Before commercial implementation, it is crucial to comprehend the diverse facets of these techniques. Progress in plant metabolic engineering may diminish fruit susceptibility to diseases. Swift cooling and low-temperature storage (at 0°C with 90-95% relative humidity) are indispensable for preserving soft fruit and necessitate integrated pre-harvest and post-harvest strategies. While emerging technologies may complement low-temperature storage and modified atmospheres, evaluating their feasibility and constraints on a commercial scale is imperative. Testing novel techniques under low-temperature conditions is essential for exploring alternatives that enhance existing methods. Further research is warranted to elucidate fruit-pathogen interactions, encompassing factors of pathogen virulence and the regulation of natural fruit-defense strategies. This information would be invaluable for the identification of candidate genes for breeding, the development of biotechnological approaches, and the establishment of consistent and efficacious methods rooted in the activation of the fruit’s innate defense system.